Synergistic Antinociceptive Effects of Ketorolac and Ascorbic Acid in a Formalin-Induced Pain Model - Josué Vidal Espinosa-Juárez; Erika Florecita Hoover-Lazo; Sergio de Jesús Rubio-Trujillo; Citlaly Natali de la Torre-Sosa; Nereida Violeta Vega-Cabrera; Josselin Carolina Corzo-Gómez; Refugio Cruz-Trujillo; Osmar Antonio Jaramillo-Morales (Future Pharmacology, 2025)
Pain is a widespread global issue and one of the most common disabling conditions in daily life. A wide range of medications are available to reduce or eliminate pain, with nonsteroidal anti-inflammatory drugs (NSAIDs) being among those most commonly used. Additionally, new analgesic approaches, such as antioxidants (Ascorbic Acid), have been explored for their potential to relieve acute pain after surgery, cancer-related pain, and chronic pain not related to cancer with fewer adverse effects. Furthermore, the use of pharmacological combinations is an alternative treatment strategy to obtain a higher efficacy using lower drug concentrations, at which side effects are minimal. Background/Objectives: The aim of this study was to evaluate the pharmacological synergism of ketorolac and ascorbic acid in an inflammatory pain model. Methods: The individual and combined effects of ketorolac and ascorbic acid were evaluated in a formalin-induced pain model in mice. Four experimental groups were established: control (vehicle), ketorolac (KET), ascorbic acid (AA), and combination (KET/AA). Results: The combination of ketorolac and ascorbic acid produced a greater antinociceptive effect compared to the vehicle and individual treatments in the formalin model. Notably, even the lowest dose of the combination (KET 6.26/AA 3.21 µg/paw) exhibited a stronger effect than the maximum doses of each individual treatment KET (100 µg/paw) and AA (100 µg/paw). The effective concentration that produced 30% of antinociception (EC30) for the tested treatments were determined, and an isobologram analysis confirmed the presence of a synergistic interaction in these combinations. Conclusions: These findings suggest that the combination of ketorolac and ascorbic acid produces a synergistic antinociceptive effect in the formalin-induced pain model. The enhanced efficacy of the combination indicates a potential therapeutic advantage in pain management by reducing the required dosage of each compound while maintaining or improving analgesic effects.